Zero Maternal Death with KECUBUNG Featured in SATE Krembung Application (Integrated Queue System) in Krembung Community Health Center in 2017 until 2018 - Arif Rahman Nurdianto (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2020)
ABSTRACTThere are some special programs in Maternal and Child Health that have not yet been reached and have a bad trend like the number of Low Birth Weight (LBW), cases of stillbirth, and babies died. There was a congenital defect in babies, increased obstetric complications, and there is one case of maternal death. There were neo-complications in infants and babies. The problem that often results in the death of pregnant women is the lack of early detection at first-level facilities in the Krembung Health center. Early detection and treatment or planning in cases of high-risk pregnant women is lacking, and then we created a SATE Krembung application in 2017. Making SATE Krembung application, socializing to the community, socializing the features of KECUBUNG to report mothers at high risk, and bringing services closer to the community and to evaluate reports from residents. Activities are collected, analyzed, and processed into mature data. The number of people activities collected during the collection of data during this research from 500 users of application from 2017 until 2018. There was a decrease in maternal mortality rates to zero patients in 2017 and 2018. The use of SATE Krembung is quite effective in reducing maternal mortality to zero patients in the Krembung health center work area, but this must be improved with the development of applications. The application of SATE Krembung with KECUBUNG feature can reduce maternal mortality by empowering health cadres and the community to be aware of the environmental conditions surrounding them.Keywords                   : SATE Krembung, KECUBUNG, Maternal Death